Self-control of Student who tend to Academic Procrastination - Dinie Thara Azhari; Yulidar Ibrahim (Jurnal Neo Konseling, 2019)
This research originate from the fact of some students that have behavior that are not appropriate students, including the procrastinating behavior to do the task. Postponement of work is called academic procrastination. Individuals who are academic procrastination, have low self-control. The purpose of this research is 1) students behavioral control who tend to academic procrastination, 2) students cognitive control who the to academic procrastination, 3) students decision making control who tend to academic procrastination. Type of research is descriptive research, that is a research which describes systematically and accurately about state of object research. Reearch subject are students at Institute of Economic Science West Sumatera Pariaman. Population of students are 434 and sample of students research are 209. Sampling technique used in research is utilizing percentage formula. Result of research indicates that students self-control in aspect of behavioral control is generally in low category, in aspect of cognitive control is generally medium category, and in aspect of decision-making control is  low category. Based on research, the students are suggested to be able to manage their time and action well, the research place is expected to open a counseling service unit so that students are be able to consult with counselors in campus.